The effect of endocrine-disrupting chemicals on placental development - Yan, Yan; Guo, Fengjun; Liu, Kexin; Ding, Rixin; Wang, Yichao (Frontiers in Endocrinology, 2023)
Chemicals known as endocrine-disrupting chemicals (EDCs) can obstruct normal endocrine signals. The EDC exposure in humans is deeply damaging during critical life phases such as pregnancy. Nonetheless, the effect of EDCs on the placenta is often underestimated. The placenta is especially sensitive to EDCs due to its abundance of hormone receptors. We evaluated the most contemporary research on the impact of EDCs on placental development and function, such as cellular invasion, fusion, proliferation, implantation, drug-transporter expression, spiral artery remodeling, and steroidogenesis. The EDCs under consideration are found in nature and have human biomonitoring data. This review also uncovers substantial knowledge gaps, which will guide future research on the subject.